Pemanfaatan Teknologi Informasi dan Manajemen Perubahan Organisasi dalam Mendukung Bisnis Berkelanjutan Pasca Covid-19 pada UMKM di Kota Bengkulu - Hafiza Tri Murti; Veny Puspita; Puspa Ratih (Jurnal Bisnis dan Pemasaran Digital, 2021)
The purpose of this study is to examine how information technology and organizational change management can be used to support sustainable business in Bengkulu City MSMEs following Covid-19. To survive the COVID-19 pandemic, the role of information technology and organizational change management is critical, as information technology serves as a manager of the information available at the time. Change management provides a structured approach for assisting individuals within an organization in transitioning from their current state to their desired state. Organizational change management is concerned with identifying groups and individuals who must change. Not only that, organizational change management entails the development of customized plans for successfully implementing the change. The primary objective of change management is to prepare for a smooth, successful transition.